Abraham in Galatians and in Genesis - S. D. Snyman (Acta Theologica)
The aim of this paper is to focus on the portrayal of Abraham in the letter to the Galatians and the book of Genesis respectively and to put it in perspective. What are the similarities and differences in the portrayal of Abraham in the Biblical books of Galatians and Genesis respectively? Three promises are made to Abraham in Genesis 12:1-3: land, progeny and blessing. It is interesting that, in each one of the passages investigated, emphasis is laid mainly (but not exclusively) on one of the promises. In Genesis 12-25, attention is paid to the promise of land and on Abraham as a blessing to the nations, but the emphasis is mainly on the problem of progeny. When Abraham resurfaces in the exilic time, the promise of the land seems to be the primary focus. In Galatians 3, the main emphasis is on blessing as the third part of the promises made to Abraham.